Setting the stage for modernity : cafés, hotels, restaurants : places of pleasure and leisure = Trendsetter der Moderne : Cafés, Hotels, Restaurants : Orte des Genusses und der Freizeit - Bollerey, Franziska, 1944-; IHAAU Institute of History of Art, Architecture and Urbanism (Berlin : Jovis, 2019)
Cafés, restaurants and hotels are at the core of the impact of modernity. With these places of taste and leisure, new architectural forms were promoted, creating the perfect setting for the public performance and image cultivation of urbanites in the emerging metropolises of the world. At the heart of many urban myths, cafés are celebrated as intangible sacred halls where works of art have been produced, revolutions plotted, lives made, and hearts broken. Cafés serve as background to public display and sociability. The novel reading of the history of the hotel offers new insight into the context of social performance, analyzing the development of tourism with its urbanization of former natural landscapes. Paris heralded the emergence of the restaurant. As a cultural institution it represents the century-old culinary tradition and as such it is an antidote to the accelerated consumption of fast food.
Industriële geschiedenis en archeologie in België (rubricering Patrick Viaene)
Includes bibliographical references (pages 234-238) and indexes.
Parallel texts in English and German.
Keywords: Restaurants -- History; Hotels -- History; Hospitality industry -- History; Hospitality industry; Hotels; Restaurants; History